Antitumor properties of certain spirooxindoles towards hepatocellular carcinoma endowed with antioxidant activity. (1st January 2020) - Al-Rashood, Sara T.; Hamed, Ahmed R.; Hassan, Ghada S.; Alkahtani, Hamad M.; Almehizia, Abdulrahman A.; Alharbi, Amal; Al-Sanea, Mohammad M.; Eldehna, Wagdy M.
Abstract: In the current medical era, spirooxindole motif stands out as a privileged heterospirocyclic scaffold that represents the core for a wide range of bioactive naturally isolated products (such as Strychnofoline and spirotryprostatins A and B) and synthetic compounds. Interestingly, no much attention has been paid to develop spirooxindole derivatives with dual antioxidant and anticancer activities. In this context, a series of spirooxindoles 6a-p was examined for their anticancer effect towards HepG2 hepatocellular carcinoma and PC-3 prostate cancer cell lines. Spirooxindole 6a was found to be an efficient anti-proliferative agent towards both HepG2 and PC-3 cells (IC50 = 6.9 and 11.8 µM, respectively). Afterwards, spirooxindole 6a was assessed for its apoptosis induction potential in HepG2 cells, where its pro-apoptotic impact was approved via the significant elevation in the Bax/Bcl-2 ratio and the expression levels of caspase-3,